PAPARAN ORGANOFOSFAT KRONIK SEBAGAI FAKTOR RISIKO GANGGUAN KOGNITIF BERDASARKAN KADAR PHOSPHORYLATED TAU SERUM - Ni Luh Putu Dirasandhi Semedi Putri,* Anak Agung Ayu Putri Laksmidewi,* I Made Oka Adnyana* (NEURONA, 2020)
INTRODUCTION CHRONIC ORGANOPHOSPHATE EXPOSURE IS PREDICTED RELATED TO DECREASED OF NEUROCOGNITIVE FUNCTION BUT THE MECHANISM IS STILL UNCLEAR ONE POSSIBLE MECHANISM IS ABNORMAL TAU PROTEIN METABOLISM AS MEASURED IN THE SERUM